Multiple oncogenic viruses identified in Ocular surface squamous neoplasia in HIV-1 patients - Bisson Gregory; Nkomazana Oathokwa; Steenhoff Andrew P; Feldman Michael; Murakami Masanao; Simbiri Kenneth O; Robertson Erle S (Infectious Agents and Cancer, 2010)
Abstract Background Ocular surface squamous neoplasia (OSSN) is a rare cancer that has increased in incidence with the HIV pandemic in Africa. The underlying cause of this cancer in HIV-infected patients from Botswana is not well defined. Results Tissues were obtained from 28 OSSN and 8 pterygia patients. The tissues analyzed from OSSN patients were 83% positive for EBV, 75% were HPV positive, 70% were KSHV positive, 75% were HSV-1/2 positive, and 61% were CMV positive by PCR. Tissues from pterygium patients were 88% positive for EBV, 75% were HPV positive, 50% were KSHV positive, and 60% were CMV positive. None of the patients were JC or BK positive. In situ hybridization and immunohistochemistry analyses further identified HPV, EBV, and KSHV in a subset of the tissue samples. Conclusion We identified the known oncogenic viruses HPV, KSHV, and EBV in OSSN and pterygia tissues. The presence of these tumor viruses in OSSN suggests that they may contribute to the development of this malignancy in the HIV population. Further studies are necessary to characterize the molecular mechanisms associated with viral antigens and their potential role in the development of OSSN.